Risk factors for bloodstream infections due to colistin-resistant KPC-producing Klebsiella pneumoniae: results from a multicenter case–control–control study. (December 2015) - Giacobbe, D.R.; Del Bono, V.; Trecarichi, E.M.; De Rosa, F.G.; Giannella, M.; Bassetti, M.; Bartoloni, A.; Losito, A.R.; Corcione, S.; Bartoletti, M.; Mantengoli, E.; Saffioti, C.; et al.
Abstract: The increasing prevalence of colistin resistance (ColR) Klebsiella pneumoniae carbapenemase (KPC)-producing K. pneumoniae (Kp) is a matter of concern because of its unfavourable impact on mortality of KPC-Kp bloodstream infections (BSI) and the shortage of alternative therapeutic options. A matched case–control–control analysis was conducted. The primary study end point was to assess risk factors for ColR KPC-Kp BSI. The secondary end point was to describe mortality and clinical characteristics of these infections. To assess risk factors for ColR, 142 patients with ColR KPC-Kp BSI were compared to two controls groups: 284 controls without infections caused by KPC-Kp (control group A) and 284 controls with colistin-susceptible (ColS) KPC-Kp BSI (control group B). In the first multivariate analysis (cases vs. group A), previous colistin therapy, previous KPC-Kp colonization, ≥3 previous hospitalizations, Charlson score ≥3 and neutropenia were found to be associated with the development of ColR KPC-Kp BSI. In the second multivariate analysis (cases vs. group B), only previous colistin therapy, previous KPC-Kp colonization and Charlson score ≥3 were associated with ColR. Overall, ColR among KPC-Kp blood isolates increased more than threefold during the 4.5-year study period, and 30-day mortality of ColR KPC-Kp BSI was as high as 51%. Strict rules for the use of colistin are mandatory to staunch the dissemination of ColR in KPC-Kp-endemic hospitals.